The Influence of Learning Facility Utilization on Learning Quality: A Quantitative Study of Public Senior High Schools in Serang Regency, Banten, Indonesia - Satiri Satiri; M. Syadeli Hanafi; Asep Muhyidin (AL-ISHLAH: Jurnal Pendidikan, 2025)
The quality of learning remains a key indicator of educational effectiveness, particularly in secondary education. One factor assumed to contribute significantly to learning quality is the effective utilization of learning facilities. However, empirical evidence quantifying this relationship in public senior high schools remains limited. This study employed a quantitative correlational design to examine the relationship between learning facility utilization and learning quality among students in public senior high schools in Serang Regency, Indonesia. Data were collected from 292 students selected through simple random sampling. A structured questionnaire was used as the research instrument. Data analysis included normality and homogeneity tests, Pearson correlation analysis, and simple linear regression. The results indicated that the data met the assumptions for parametric analysis. A strong positive relationship was found between learning facility utilization and learning quality (r = 0.85). The regression analysis produced the equation Ŷ = 30.72 + 0.70X, indicating that increased utilization of learning facilities was associated with higher learning quality. The coefficient of determination (R² = 0.85) showed that 85% of the variance in learning quality was explained by learning facility utilization. The t-test confirmed that this relationship was statistically significant at the 0.01 level. These findings demonstrate that effective utilization of learning facilities plays a crucial role in improving learning quality. Optimizing school facilities can therefore enhance the effectiveness of teaching and learning processes and should be prioritized in educational management and policy development.